Organizational Culture - Work Behavior Association: Administrative Analysis in a Stated Owned Company, Central Java - Kuntariningsih, Apri; Mariyono, Joko (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
This study aimed to analyze organizational culture, the work behavior of production employees, and the relationship between organizational culture and employees' work behavior in coffee production. Determining the research location was purposely done considering that the factory is an active factory operating in producing and processing agricultural products. Respondents in this study used the survey method, in which collect 101 sample of field labors from the population. Data collection was done by interview using a questionnaire. Analysis of the data used is a correlation. The organizational culture analyzed here includes the production process, payment of employee salaries, the value of the type of work, rules, beliefs held in work, decision-making processes, and taboos. The results showed that organizational culture in the form of rules, payment of employee salaries, work beliefs adopted at work, decision-making processes, and taboos simultaneously affected employee work behavior. In contrast, the value of work type had no relationship to employee work behavior. The company should provide training and rewards for employees to improve employee work behavior and enhance employee performance.